Analisis Aktivitas Pertambangan Pasir di Korong Ganting Kecamatan Lubuk Alung Kabupaten Padang Pariaman Perspektif Etika Bisnis Syariah - Fadilla Turahma; Asyari (ARZUSIN, 2026)
Although sand mining activities have been widely studied because they provide economic benefits while potentially causing environmental impacts, research specifically analyzing these practices from the perspective of Sharia Business Ethics at the local community level remains relatively limited. This study aimed to analyze sand mining activities in Korong Ganting, Lubuk Alung Subdistrict, Padang Pariaman Regency, and assess their conformity with the principles of Sharia Business Ethics. The study employed a qualitative approach with a case study design. The research informants consisted of mining business operators, mine workers, the nagari government, and surrounding community members selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that sand mining activities had been conducted for approximately fifty years and had become one of the community’s main sources of livelihood. These activities provided economic benefits and helped reduce river sedimentation but had not yet been supported by an administrative recommendation from the nagari government and were still conducted traditionally using simple equipment. From the perspective of Sharia Business Ethics, these mining practices had provided maslahah for the community, but the implementation of the principles of trustworthiness, responsibility, and governance consistent with Sharia values still needed to be strengthened. This study contributes to the development of research on Sharia Business Ethics in natural resource management and provides practical implications for the government and the community in improving mining governance that is responsible, sustainable, and aligned with Sharia principles.